Coronavirus disease 2019 and pediatric anesthesia. Issue 3 (June 2021) - Tan, Jonathan M.; Disma, Nicola; Matava, Clyde T.
Abstract : Purpose of review: The purpose of this review is to provide the latest evidence for delivering safe and effective anesthesia care for pediatric patients with coronavirus disease 2019 (COVID-19) and to highlight continuing gaps in the literature. Recent findings: Safe and efficient care of pediatric patients with COVID-19 can be delivered with the proper planning, coordination, supplies, and staff preparation. From the start of the pandemic, pediatric anesthesiologists from around the world contributed important insights and shared experience as to how best to adapt anesthesia care for children with COVID-19 requiring general anesthesia and sedation. Although initial efforts focused on creating safe airway management processes, the role of anesthesiologists as perioperative leaders quickly extended to ensuring well-coordinated management of COVID-19 patients throughout the hospital for procedures, including preprocedure testing, patient transport, operating room setup, and ensuring the safety of staff. Several important areas remain not well studied including, the timing of rescheduling elective procedures following COVID-19 infection, the perioperative implications of re-infection, and future considerations of managing vaccinated children. Summary: Pediatric anesthesia care can be safely delivered to children with COVID-19 and after COVID-19 infection. More attention needs to be focused on the perioperative management of COVID-19 children in recovery requiring anesthesia.